2009 Global Information Infrastructure Symposium 2009
DOI: 10.1109/giis.2009.5307097
|View full text |Cite
|
Sign up to set email alerts
|

Voicing-aware parametric speech quality models over VoIP networks

Abstract: This paper describes novel parametric speech quality models which subsume the effect of packet loss distribution and voicing feature of missing signal waves. Speech quality estimate models for voiced and unvoiced loss location patterns are developed following multiple statistical regression analysis of measurements gathered from a built speech quality assessment framework. The overall speech quality is estimated by combining voiced and unvoiced speech quality estimate scores using an expression calibrated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Jelassi et al [32] extended the conventional parametric speech quality estimation models by considering the voicing feature of lost packets. This model builds a voicing-aware speech quality model that allows to accurately quantifying the effect of lost packets according to their voicing property.…”
Section: Hybrid Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jelassi et al [32] extended the conventional parametric speech quality estimation models by considering the voicing feature of lost packets. This model builds a voicing-aware speech quality model that allows to accurately quantifying the effect of lost packets according to their voicing property.…”
Section: Hybrid Algorithmsmentioning
confidence: 99%
“…GMM are used, again, to generate an artificial reference model that is compared with the transmitted speech signal. On the other hand, a parametrical analysis similar to the previous one [32] is performed, evaluating the VoIP header. Consequently, this model inherits the limitations discussed above, related to the relevance of ignored impairments such as delay or jitter.…”
Section: Hybrid Algorithmsmentioning
confidence: 99%
“…As such, there is no subtle characterization and specification of the burstiness of the packet loss processes. This could lead to a wrong judgment of perceived quality because it has been subjectively observed that two distinct bursty packet loss patterns with identical PLR may lead to an obvious difference in the perceived quality [7]. Moreover, the rapidity of the exponential decay/growing is hold static independently of the duration of preceding Good or Bad state and the magnitude variation of previous and current packet loss ratios.…”
Section: Vqmon: Voice Quality Monitoringmentioning
confidence: 99%
“…These methodologies, so-called generate an artificial reference model that is compared with the transmitted speech signal. On the other hand, a parametrical analysis similar to previous[98] is performed, evaluating the VoIP header. Consequently, this model inherits the limitations discussed above, related to the relevance of ignored impairments such as measure the difference between the received and the reference speech signals.…”
mentioning
confidence: 99%